Cover, Table of Contents, Editorial and Reviewer Team of Jurnal Adipati Vol. 4 No. 1 2025 - Dwicahyani, Anindya Rachma (Jurnal Pengabdian Masyarakat dan aplikasi Teknologi, 2025)
Supporting Documents for Jurnal ADIPATI Vol. 4 No. 1 2025 consisting of: Cover, Table of Contents, Editorial Team, Reviewer Team.